2022
DOI: 10.35870/jtik.v6i4.569
|View full text |Cite
|
Sign up to set email alerts
|

Sentimen Analisis Masyarakat Indonesia di Twitter Terkait Metaverse dengan Algoritma Support Vector Machine

Abstract: Metaverse is part of the increasingly rapid development of technology in the world, bringing the virtual world into the real world is very possible. Starting from a novel, metaverse has now begun the process of being implemented, especially with the COVID-19 pandemic being one of the strong foundations for speeding up the implementation of this technology. Since the emergence of the metaverse echoed by Facebook, which has changed its name to meta, has made the world's public attention increasingly highlight th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 2 publications
0
7
0
2
Order By: Relevance
“…Instead of a survey, the focus of our work is to use data visualization and machine learning to analyze and predict metaverse sentiment. Ahmad and Gata [11] analyzed the sentiment of Indonesian people towards the metaverse. They found that majority (66%) of the people showed neutral sentiment towards the technology and the remaining population were split between positive (16%) and negative (17%).…”
Section: Related Workmentioning
confidence: 99%
“…Instead of a survey, the focus of our work is to use data visualization and machine learning to analyze and predict metaverse sentiment. Ahmad and Gata [11] analyzed the sentiment of Indonesian people towards the metaverse. They found that majority (66%) of the people showed neutral sentiment towards the technology and the remaining population were split between positive (16%) and negative (17%).…”
Section: Related Workmentioning
confidence: 99%
“…Sentiment analysis is an analysis technique that can be used to determine and measure the attitudes or emotions of each user toward a topic. In this context, sentiment analysis of Twitter users regarding metaverse technology may involve collecting and analyzing tweets about the metaverse to determine whether Twitter users generally show a positive, negative, or neutral attitude toward the topic (Ahmad & Gata, 2022). Previous research on Lexicon-based sentiment analysis usually focuses on how this method can be used for sentiment analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The Metaverse technology began to be widely discussed when the founder of Facebook, Mark Zuckerberg, officially transformed his product with the name Meta. His ideas regarding this technology were submitted at the end of June 2021 [1]. Metaverse is a threedimensional virtual world technology where Avatars or our profile representations in that world can carry out social, political, economic and cultural activities [2].…”
Section: Introductionmentioning
confidence: 99%